Critical Synthesis Package: OPTION (Observing Patient Involvement in Shared Decision Making) - Deborah L. Engle (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Observing Patient Involvement in Shared Decision Making (OPTION) measure, and (2) a copy of the OPTION and supplementary files developed by Glyn Elwyn MD, PHD, MSc, FRCGP, and co-developers Professor Adrian Edwards, Professor Kerry Hood, Mike Robling, MD, Michel Wensing, MD, and Professor Richard Grol. The OPTION observational tool was developed to assess the extent to which health care providers involve patients in decision-making processes. The OPTION consists of 12 items representing key patient-involving behaviors that measure a single factor labeled Shared Decision Making. For each survey item, behaviorally-based response options are presented on a 5-point Likert-type scale, ranging from 0 to 4, where baseline behavior is set at 2. While assessing a clinical encounter (either audio or video), two observers/raters score each OPTION item. Each of the rater's scores is summed, and the mean of the sum scores is calculated. The mean sum score is then transformed to a score that lies between 0 and 100. This scaled score represents the total OPTION score, where higher scores indicate a higher level of the healthcare provider's involvement of the patient when decision making occurs. The OPTION measure has been a widely-used across clinical contexts and in several languages. Yet, on a psychometric basis, there have been limitations with the OPTION measure noted in some studies. These limitations include significant variation in interrater agreement at the item level, its single-factor structure, and insufficient reliability for the assessment of the individual as opposed to group performance. At the conceptual level, limitations include an inability to elicit patient preference for involvement, and the rarity for providers to achieve higher levels of performance.